Understanding the Practices of Strategic CSR in Controversial Industry: Case of Tobacco Company in Indonesia - Yasmine, Shafira Mourina; Swara, Vandy Yoga (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2022)
How do tobacco companies take responsibility for social issues under the business existence on health problems and economic issues. The research focuses on a small amount of research in corporate social responsibility (CSR) duty under Tobacco Company. Through the Sampoerna Retail Community (SRC), PT HM Sampoerna Tbk shows a different takes problem-solving of CSR on controversial issues. Through qualitative research, the data, primary data (interviews and observations) and secondary data (documentation studies), coded and analyzed using keywords derived from theory. This study found that CSR in cigarette companies is a form of controversial industrial business strategy that departs from considering business processes' internal and external conditions. The results show SRC is a way for companies to be socially responsible by articulating external conditions (outside-in) dominated by public restrictions on tobacco products and as an internal strategy (inside-out) that departs from the logic of business sustainability. SRC is a form of company compliance with several state regulations, restricting cigarette products and preventing children's access to cigarettes as an outside-in strategy. In the inside-out context, SRC is the company's strategy to ensure all consumers can reach products, collaborating with Fast Moving Consumer Goods (FMCG) companies as an alternative to the uncertainty of controversial industry conditions, and reducing CSR costs.